Production and Characterization of Thermoalkaliphilic Xylanase from Bacillus halodurans CM1 on Degumming Process of Ramie (Boehmeria nivea L.Gaud)Fiber as Textile Raw Material - DEWI NANDYAWATI; DEA INDRIANI ASTUTI; NIKNIK NURHAYATI; ASEP RISWOKO; IS HELIANTI (Microbiology Indonesia, 2021)
Ramie fiber is a potential raw material to substitute imported raw materials such as cotton. Due to its higher hemicellulose content, ramie fiber required hydrolysis in a process called degumming. Enzymatic degumming is environmentally friendly compared to traditional process which using chemicals. Alkalithermophilic xylanase have high ability in hemicellulose hydrolysis. The production of xylanase was conducted by submerged fermentation of Bacillus halodurans CM1 in 20L bioreactor using Mamo and corncob medium with optimum conditions at 50°C, pH 9, 150 RPM and 1 vvm. The optimum specific activity of xylanase measured by Bailey method at 70°C and pH 9 is 475.41 U/mg. Xylanase was stable at 50°C, pH 9 and relatively stable to K+, Na2+, Co2+ and Ca2+ metal ions and Triton-X, Saba dan Tween-80 surfactants. Degumming process was carried out by immersing ramie fibers in formulated degumming solution with vlot 1:20 at 50°C, 150 RPM and 180 minutes. The enzymatic degumming process may substitute or reduce the use of chemicals due to its significant effect on ramie fiber quality. Enzymatic and chemical degumming process reduce the weight of Ramie Fiber to 7.23 %, and 7.72 %, slightly higher than enzymatic degumming 7.15%. Enzymatic degumming maintains tensile strength at 27.51 %. Whiteness index enhanced to 2.99% enzymatically and 3.49% chemically. Keywords: Bacillus halodurans CM1, enzymatic degumming, ramie fiber, textile industry, thermoalkaliphilic xylanase